The Use of Keystone Flaps in Periarticular Wound Closure: A Case Series - Jovic, Thomas H.; Jessop, Zita M.; Slade, Robert; Dobbs, Thomas; Whitaker, Iain S. (Frontiers in Surgery, 2017)
The Keystone perforator island flap (Keystone flap), is a Type A fasciocutaneous advancement flap, consisting of two V to Y advancement flaps. Skin cancer excision around joints presents a number of reconstructive challenges. Owing to the mobile nature of joints, the optimal periarticular reconstructive option should possess the ability to provide adequate tissue coverage and withstand regional changes in tensile pressures. We report a single-surgeon series of five cases of periarticular keystone flap between 2014 and 2017. Data were collected from operation notes, clinical photography, histopathology, and outpatient clinic records. The indication for keystone flap was skin cancer in all cases (n = 5). The largest defect size post-excision in was 75 mm × 40 mm × 15 mm. All keystone flaps demonstrate a color and cosmetic appearance comparable to adjacent tissue. There were no major postoperative complications including flap failure or impaired range of joint movement in the follow up period. Superficial wound infection occurred postoperatively in one case. This is the first case series to discuss the use of keystone flaps in periarticular wound closure. Locoregional fasciocutaneous wound coverage offered by keystone flaps may alleviate the risks of graft failure, contour defects, and donor site morbidity associated with alternative reconstructive options, with good functional and cosmetic outcomes. We advocate their use as a robust reconstructive option in periarticular areas.